2014
DOI: 10.1515/sg-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental strategies for clonal eucalyptus

Abstract: The success of any forestry operation depends on the careful choice of the clones to be planted. At existing yield levels, the differences among clones are becoming smaller, leading to the need to use experimental strategies for a more successful choice. To obtain information in regard to better experimental strategies, data from two clonal tests of eucalyptus were used. One of the tests consisted of 35 clones and another of 48 clones. In both tests, the experimental plot consisted of 100 plants at commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…There is not much information in this regard (RESENDE, 2002). However, the results show also that there were no big variations in the classification of treatments using plots of one plant compared to plots ranging from five to even 100 plants (ANDRADE et al, 2006;MENDES et al, 2014).…”
Section: Resultsmentioning
confidence: 79%
“…There is not much information in this regard (RESENDE, 2002). However, the results show also that there were no big variations in the classification of treatments using plots of one plant compared to plots ranging from five to even 100 plants (ANDRADE et al, 2006;MENDES et al, 2014).…”
Section: Resultsmentioning
confidence: 79%
“…Essas metodologias são empregadas frequentemente em diversas culturas, como cana-de-açúcar (Leite et al, 2009); melão (Dias, 2013); eucalipto (Mendes et al, 2014); tabaco (Toledo et al, 2013); mamão (Lima et al, 2007); sorgo (Lopes et al, 2005); milho (Cargnelutti Filho et al, 2011); café (Moraes, 2013) simulações, para cada tamanho de parcela, identificou-se a tendência da acurácia, sendo que o valor aumenta à medida que a quantidade de plantas em cada parcela aumenta. O comportamento desses dados resultou numa equação ajustada pelo modelo de Gompertz, e o possível ponto em que ocorre a mudança de curvatura é com 50 plantas, sendo de 0,70 a estimativa de acurácia seletiva média nessa condição.…”
Section: Resultsunclassified
“…Com as facilidades computacionais disponí-veis atualmente, os trabalhos de simulação tornaramse mais frequentes nos programas de melhoramento (Moraes, 2013;Toledo et al, 2013;Mendes et al, 2014). Uma das áreas em que a simulação ainda tem muito a contribuir é na avaliação de alternativas visando a melhoria da precisão experimental, entre elas a escolha do tamanho ideal das parcelas.…”
unclassified
“…For other spacings, the rank coincidences were always low. Mendes et al (2014), working with eucalyptus, estimated rank coincidence above 90% and found 55 plants for plot size.…”
Section: Study Of Parameters Through Bootstrappingmentioning
confidence: 99%
“…In other species, such as Eucalyptus, it has already been confirmed that decreases in plot size from 100 to 25 plants does not affect accuracy of selection and experimental precision, and such decreases may reduce costs in the breeding program (17). Working with brachiaria grass, Dias et al (2014) measured fresh biomass volume and carried out analysis through the bootstrapping method and the maximum curve of the coefficient of variation.…”
Section: Study Of Parameters Through Bootstrappingmentioning
confidence: 99%